ADDED VALUE ANALYSIS OF LUGU'S ORGANIC PREMIUM TEA AGROINDUSTRY IN GUNUNG TALANG DISTRICT, SOLOK REGENCY - Aerini Dewanti; Dwi Evaliza; Rika Hariance (RADJA PUBLIKA, 2026)
In Indonesia, the tea processing agroindustry is dominated by large plantation companies. This research is motivated by farmers who are members of a cooperative that processes tea on a small scale and has successfully exported its products abroad. Therefore, this study aims to analyze the added value of the tea products produced in order to compete effectively with other companies. The analysis was carried out quantitatively using the Hayami method. Observations were conducted on the processing of tea leaves into dried tea products (black, green, and white tea). The results indicate that all three tea variants generate positive value-added. Black tea, green tea, and white tea yield value-added of Rp 23,080, Rp 41,201, and Rp 142,395 per kilogram, respectively. Notably, white tea demonstrates the highest value-added, with a profit of Rp 115,216/kg, while black tea and green tea generate profits of Rp 22,980/kg and Rp 41,075/kg, respectively. These findings are expected to provide valuable insights for tea farmers and agroindustry stakeholders in optimizing tea plantation management, improving operational efficiency, and maximizing profitability.